Eurozone exit risk - Stefan Eichler; Ingmar Rövekamp (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
In the course of eurozone exit, the underlying stocks of American Depositary Receipts (ADRs) would be redenominated from euros into the new national currency. We exploit ADR investors' exposure to currency redenomination losses to derive a novel measure of eurozone exit risk. We find that while domestic bank stocks are not significantly affected by domestic exit risk, there is a negative exposure to exit risk of other countries that is channeled through bilateral credit risk. For the real sector, exposure to eurozone exit risk is heterogeneous among industries and is less negative for more indebted companies.
urn:nbn:de:bsz:14-qucosa-226362
Keywords: F31; F32; G01; G12; G15; 330; Eurozone Exit Risk; American Depositary Receipts